External Debt And Economic Growth Nexus: Evidence From Malaysia, Thailand And Philippines - Lau, Evan; Lee, Alvina Syn-Yee; Ahmad Zubaidi, Baharumshah (IISES, 2015)
This study aims to examine the contribution of external debt to economic growth in three countries namely; Malaysia, Thailand and the Philippines. To discern the causal chain linkages among the I(1) macroeconomic variables typically utilized to test the connection between external debt and economic growth, several econometric procedures are employed in this study. By employing the cointegration test, the results reveal the existence of one unique long-run relationship among the variables for Malaysia while two cointegrating vectors are identified for both Thailand and the Philippines. From the results, it is evident that both the growth-driven exports and export-led growth hypothesis exist in Malaysia and Thailand respectively. The dynamic econometric analysis finds that exports of goods and services appear to be the most leading variable beyond the sample for the next 50 years. The findings from the study recommend the policy makers should formulate effective debt management policies to monitor the amount of external borrowings so that the accumulation of external debt will not hinder the economic growth.